Knowledge and Attitude of Iranian Dentists towards Cone-Beam Computed Tomography - Ghoncheh, Zahra (Front Dent, 2019)
OBJECTIVES: We aimed to evaluate the knowledge and attitude of Iranian dentists towards cone-beam computed tomography (CBCT). MATERIALS AND METHODS: A 20-item questionnaire was distributed among 410 Iranian dentistry graduates attending the 56th Congress of Iranian Dental Association held in Tehran, Iran. The questionnaire included items on demographic characteristics, namely full name, age, gender, work experience, type of current activity (individual or group), and the highest educational level. In addition, the questionnaire contained items on the knowledge and attitude of dentists. The obtained data were analyzed using statistical tests. RESULTS: In this study, 49.3% and 22.4% of the subjects were male and female, respectively, 47.1% of whom used CBCT, while 49.8% did not. In detail, 72.2% of the dentists used the technique to evaluate the location of implants, whereas 19.7%, 3.2%, and 2.7% of the subjects applied it to localize the inferior alveolar nerve (IAN), evaluate the location of implants and localize the IAN, and perform cephalometric analysis, respectively. The main causes of lack of prescription of CBCT entailed high cost (80%), high rate of patient absorbed dose (27.6%), insufficient number of CBCT centers (46.3%), and the long duration of the process (15.6%). CONCLUSION: CBCT is an advantageous imaging technique in dentistry. Considering the increased application of CBCT in dentistry, attending workshops could help train dentists to use the technique.